2005
DOI: 10.1002/jbm.a.30535
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of in vivo endothelialization of tissue‐engineered vascular grafts by granulocyte colony‐stimulating factor

Abstract: Successful reconstruction of large-diameter blood vessel in humans has been demonstrated using the tissue engineering technique, but improvement in patency of small-diameter bioartificial vascular graft remains a great challenge. This study reports that granulocyte colony-stimulating factor (G-CSF) can enhance in vivo endothelialization of tissue-engineered vascular grafts, which could be used to improve patency of small-diameter vascular graft. Vascular grafts were tissue engineered with decellularized canine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 32 publications
3
49
0
Order By: Relevance
“…Synthesized cDNA was amplified by PCR using the primers shown in Table 1. 32 For amplification, the following thermocycler program was used: 94°C for 2 min, 94°C for 30 s, annealing 60°C for 30 s, 72°C for 30 s, and 72°C for 10 min, repeated for 40 cycles from step 2 to step 4. The PCR products were resolved on 1.5% agarose gels (containing ethidium bromide at 0.5 mg/mL) and revealed at UV light.…”
Section: Rt-pcr and Western Blot Analysesmentioning
confidence: 99%
“…Synthesized cDNA was amplified by PCR using the primers shown in Table 1. 32 For amplification, the following thermocycler program was used: 94°C for 2 min, 94°C for 30 s, annealing 60°C for 30 s, 72°C for 30 s, and 72°C for 10 min, repeated for 40 cycles from step 2 to step 4. The PCR products were resolved on 1.5% agarose gels (containing ethidium bromide at 0.5 mg/mL) and revealed at UV light.…”
Section: Rt-pcr and Western Blot Analysesmentioning
confidence: 99%
“…While large diameter TEVG grafts regenerated successfully in humans with a five-years patency of about 90 % [5], small diameter vascular grafts (diameter < 5 mm) are still a challenge [6]. Among the main reasons for graft failure of small diameter grafts (anastomotic intimal hyperplasia, aneurysm formation, infection, and progression of atherosclerotic disease), acute thrombogenicity of the graft is one of the most important [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that BMCs are capable of differentiating into ECs [35][36][37] and vascular SMCs. [38][39][40] Indeed, BMCs have been shown as a feasible cell source for the engineering of cardiovascular tissues in animals 7,9,[16][17][18] and humans. 41,42 In addition, the use of BMCs as a cell source for vascular graft engineering is considered less invasive than harvesting vascular cells from autologous blood vessels.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] In brief, bone marrow (30 mL per dog) was aspirated from the humeri of healthy mongrel dogs (12 months old, 20-25 kg, n 5 7) with a syringe containing heparin (100 units heparin/mL bone marrow). Aspirated bone marrow was mixed with an equal volume of phosphate-buffered saline (PBS, Sigma, St. Louis, MO) solution and centrifuged on Ficoll-Paque density gradient (Amersham Biosciences, Arlington Heights, IL) for 30 min at 2000 rpm.…”
Section: Bmc Isolation and Culturementioning
confidence: 99%